Density of States of a Nanoscale Semiconductor Interface as a Transduction Signal for Sensing Molecules - Pinzon, Edgar F. [UNESP]; Santos, Adriano Dos [UNESP]; Bueno, Paulo R. [UNESP] (American Chemical Society (ACS), 2021)
Nanoscale inorganic semiconductors (with interfacial thickness <10 nm) have superior stability compared to soft organic compounds and are important for the development of enhanced reagentless sensing devices. As a proof of concept, this study demonstrated that the density of states of a copper oxide mixed valence semiconducting nanoscale film can be suitably designed as a transducer signal for reagentless sensing of phenol.
Keywords: density of states; electrochemical capacitance; Fermi level; phenol sensing; semiconductor interface